2006
DOI: 10.1159/000091606
|View full text |Cite
|
Sign up to set email alerts
|

<i>L</i>-Arginine Supplementation Prevents the Development of Endothelial Dysfunction in Hyperglycaemia

Abstract: Diabetes mellitus leads to the development of endothelial dysfunction which finally contributes to diabetic angiopathy. We investigated the effects of hyperglycaemia on nitric oxide (NO) liberation and a possible influence of L-arginine supplementation. Porcine endothelial aortic cells (PAEC) were cultured in Medium 199 containing 0.33 mmol/l L-arginine. During the entire third culture passage (= 4 days) cells were either exposed to 5 or 20 mmol/l D-glucose with or without additional 3 mmol/l L-arginine. For o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…An antioxidative property of NO has been reported by some investigators [23,24]. Furthermore, some studies revealed the protective effects of the NO-generating compounds L-arginine and sodium nitroprusside in STZdiabetic rats [25,26]. NO seems to be a potential antioxidant in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…An antioxidative property of NO has been reported by some investigators [23,24]. Furthermore, some studies revealed the protective effects of the NO-generating compounds L-arginine and sodium nitroprusside in STZdiabetic rats [25,26]. NO seems to be a potential antioxidant in the present study.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, in vitro studies on hyperglycemia assessing various characteristics of different cell types found effects in the hyperglycemia group, whereas no effects were described in both osmotic control groups, neither L-glucose-supplemented nor mannitol-supplemented. 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with L-arginine (a substrate of NOS) seems able to rebalance NO production on the dysfunctional endothelium, stimulating NOS activity both directly and indirectly: antagonizing the effects of ADMA and reducing endothelin-1 synthesis (41). Lerman et al (42) found a significant improvement in endothelial function in patients with coronary artery disease after 6 months of L-arginine supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Lerman et al (42) found a significant improvement in endothelial function in patients with coronary artery disease after 6 months of L-arginine supplementation. Treated patients showed a better vasodilatory response after acetylcholine induced contraction and reduced endothelin-1 plasmatic levels.…”
Section: Introductionmentioning
confidence: 99%